The efficacy of mechanical thrombectomy for severe basilar-artery occlusion - Ito, Ayumi; Hagiwara, Kazuki; Matsumoto, Gaku; Matsumoto, Takashi; Mitsui, Daichi; Miyazaki, Yoshibumi; Iwase, Fumiaki; Umeda, Kosuke (KANTO Journal of Japanese Association for Acute Medicine, 2023)
The efficacy of mechanical thrombectomy (MT) for severe ischemic stroke of posterior circulation is unclear despite the established effectiveness for anterior circulation. Therefore we analyzed the efficacy of MT for severe basilar-artery occlusion. We defined “severe” basilar-artery occlusion as National Institutes of Health Stroke Scale (NIHSS) ≥22 and Glasgow Coma Scale (GCS) ≤8. Fourteen patients were enrolled. Median age, NIHSS and GCS were 72, 38 and 4, respectively. Modified Rankin Scele≤3 occurred 3 of 14 patients. Mortality rate was 57%. Though the efficacy was not sufficient, MT seems to be important when we take the severity into consideration.